2017
DOI: 10.1063/1.4984081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscosity on droplet-droplet collisional interaction

Abstract: A complete knowledge of the effect of droplet viscosity on droplet-droplet collision outcomes is essential for industrial processes such as spray drying. When droplets with dispersed solids are dried, the apparent viscosity of the dispersed phase increases by many orders of magnitude, which drastically changes the outcome of a droplet-droplet collision. However, the effect of viscosity on the droplet collision regime boundaries demarcating coalescence and reflexive and stretching separation is still not entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…In particular, understanding the effect of viscosity and surface energy on binary droplet collisions is of great importance for understanding the outcomes of binary equal-sized droplet collision. The dynamics of binary equal-sized droplet collision has been investigated by numerous experimental and numerical studies (e.g., Ashgriz & Poo 1990;Finotello et al 2017). proposed the criteria for collisional sticking as follows:…”
Section: Resultsmentioning
confidence: 99%
“…In particular, understanding the effect of viscosity and surface energy on binary droplet collisions is of great importance for understanding the outcomes of binary equal-sized droplet collision. The dynamics of binary equal-sized droplet collision has been investigated by numerous experimental and numerical studies (e.g., Ashgriz & Poo 1990;Finotello et al 2017). proposed the criteria for collisional sticking as follows:…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods are not well adapted to describe topological changes of the interface, like coalescence and breakup phenomena. In the VOF method, coalescence happens automatically when two approaching interfaces share a common grid cell [13]. The Level-set method has similar problems: coalescence either happens automatically or it is not possible unless it is explicitly imposed [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from the kinetic energy evolution curve, it can be observed the kinetic energy at the final time was always less than 10% of the initial kinetic energy. The research of Finotello et al [23] showed that a collision can be considered completed when the residual kinetic energy was negligible. In Figure 12b, at the initial stage, as the surface tension decreases, the dissipated energy increases, so the coalescence time of the droplets in Figure 8 is delayed.…”
Section: Energy Evolutionmentioning
confidence: 99%
“…For binary Newtonian droplet collisions, the current studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] are mainly focused on two aspects: from binary low-viscosity droplet collisions to binary high-viscosity droplet collisions, and from binary homogeneous-droplet collisions to binary heterogeneous-droplet collisions. Jiang et al [9] and reflexive separation of droplets were investigated.…”
Section: Introductionmentioning
confidence: 99%